Impact of artistic gymnastics on bone formation marker, density and geometry in female adolescents: ABCD-growth study - Exupério, Isabella Neto [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Werneck, André Oliveira [UNESP]; Maillane-Vanegas, Santiago [UNESP]; Luiz-de-Marco, Rafael [UNESP]; Mesquita, Eduardo D.L. [UNESP]; Kemper, Han C.G.; Fernandes, Rômulo Araújo [UNESP] (Korean Society for Bone and Mineral Research, 2019)
Background: To compare bone density accrual and markers of bone geometry and formation between female adolescents engaged and not engaged in artistic gymnastics (AGs). Methods: This was a 12-month longitudinal study involving 20 female adolescents, including 10 controls and 10 gymnasts (AGs) aged 11 to 16 years. At baseline, the gymnasts had a minimum of 12 months of practice, and the controls reported no participation in any organized sport. Bone mineral density (BMD) was measured in the lower limbs, upper limbs, spine, and whole body. In addition, BMD and geometrical properties of the femur were assessed. As a bone formation marker, osteocalcin level was measured. Results: Femoral aspects were increased in the gymnasts by 19% (P= 0.009), 14% (P= 0.047), and 10% (P= 0.046) in the Ward’s triangle, trochanter, and the overall bone, respectively, than in the control girls. Geometrical parameters, bone accrual, and osteocalcin levels were similar in both groups. The weekly training load explained 30.8% of all bone gains on the lower limbs and affected the density on parts of the femur. Conclusions: The gymnasts, after a 12-month follow-up, demonstrated a higher BMD in the Ward’s triangle and whole femur than the controls, as well as an improvement in femur density. These changes were mainly due to the weekly training load. Lastly, the gymnasts had significant bone accrual (after 12 months) in the upper limbs, lower limbs, and whole body.
Keywords: Adolescent; Bone and bones; Growth; Gymnastics; Sports